Performance Appraisal: Appraiser’s Discomfort and Stress - Dr. Poonam Vats; Dr. Pooja Wadhawan; Anukriti Dixit; Shruti Arora (International Journal of Indian Psychȯlogy, 2022)
Performance appraisal comprehensively evaluates employee performance with regard to his or her performance on the job and his/her potential for development. Providing someone a sincere candid evaluation based on the measurement is a taxing experience for most evaluators. Combative behaviour on the part of the person acting as an evaluator is frequent. Workplace stress then is the harmful physical and emotional response that can happen when there is a conflict between job demands and the amount of control an appraiser has on the employee. This study examines the correlation between discomfort and general work stress among managers and senior managers during the period of appraisal (N=76, Sample location: Delhi NCR, Experience: 8-10 years). The study follows a cross-sectional research design. For the purpose of this study the two statistical tools employed were Performance Appraisal Discomfort Scale and General Work Stress Scale. A moderate correlation was established between discomfort and stress, experienced by appraisers, which highlighted their substantial relationship.  It preaches extensive knowledge and awareness of the discomfort experienced from the employers’ point of view when administering performance appraisal.